Introduction of Superior Varieties and Seeds Quality in Shallot Cultivation in "Sumber Hidup" the Farmer Group Sigerongan Village - Hemon, A. Farid; Kisman, Kisman; Sudarmawan, AA Ketut; Ujito, Lestari (Unram Journal of Community Service, 2024)
Members of the "Sumber Hidup" farmer group mostly carry out farming on narrow fields of land with very low yields. One alternative for developing farming businesses on limited land was the use of superior varieties and quality seeds of shallot. To achieve this goal, activities have been carried out to apply science and technology, both in the training/counseling and plot demonstrations (action research) for farmers. The method used in training was adult education with participatory techniques. The resulting output was an increase in the skills and knowledge of partner farmers. The demonstration plot that has been carried out was action research based on the results of research that has been carried out previously. The demonstration plot that has been done was to compare the planting of superior varieties of shallots with shallot seeds originating from farmers. The results of the activity showed that members of the "Sumber Hidup" farmer group who participated in the extension were very responsive to community service activities. Farmers heard and asked several questions related to planting superior varieties and quality shallot seeds on limited land. Participants were very active in every activity such as selecting seeds, making demonstration plots, planting, hilling, weeding and harvesting activities. The process of technological transformation of the use of superior varieties and quality seeds of shallots on limited land has occurred in the "Sumber Hidup" farmer group. The results of the demonstration plot showed that superior varieties produced 5-7 tons per hectare of shallot